Tracing and regulating redox homeostasis of model benthic ecosystems for sustainable aquaculture in coastal environments - Shono, Nobuaki; Ito, Mana; Umezawa, Akio; Sakata, Kenji; Li, Ailong; Kikuchi, Jun; Ito, Katsutoshi; Nakamura, Ryuhei (Frontiers in Microbiology, 2022)
Aquaculture in coastal environments has an increasingly important role in the world’s food supply; however, the accumulation of organic compounds on seafloors due to overfeeding adversely affects benthic ecosystems. To assess the ecological resilience of aquafarms to nutrient influx, we investigated the redox homeostasis of benthic ecosystems using a marine oligochaete as a model benthic organism in aquaculture fields. Real-time monitoring of the redox potential of a model benthic ecosystem constructed in an electrochemical reactor allowed evaluation of the homeostatic response of the system to nutrient addition. Although the detrimental effects of overfeeding were confirmed by irreversible potential changes in the sediment, redox homeostasis was reinforced through a symbiotic relationship between oligochaetes and sediment microorganisms. Specifically, the oligochaetes exhibited reversible changes in metabolism and body position in response to dynamic changes in the sediment potential between -300 and 500 mV, thereby promoting the decomposition of organic compounds. The potential-dependent changes in metabolism and body position were reproduced by artificially manipulating the sediment potential in electrochemical reactors. Given the importance of benthic animals in sustaining coastal ecosystems, the electrochemical monitoring and physiologic regulation of marine oligochaetes may offer an intriguing approach towards sustainable aquaculture.